Effects of inoculation training on stress, anxiety, and coping strategies among postgraduate students of the Faculty of Educational Studies - Esfahani, Tahereh Mirhakak (2014)
Anxiety and stress are the main concerns of human being, especially for postgraduate students. Both anxiety and stress disturb life balance and can lead to lower levels of their performance. Stress is the body's reaction to a change that requires a physical, mental or emotional adjustment or response.Stressreflects experience of stressors in postgraduatestudents, can create psychological and physiological reactions that occur in the face of stressors. Anxiety is a dimension of stress occurring in response to external as well as internal stimuli and can lead to behavioral, cognitive, emotional, and physical symptoms for postgraduate students. High stress levels in postgraduate students lead to anxiety, poor academic performance, attrition, and serious health problems. This study was designed based on the application ofStress Inoculation Training (SIT) program, as developed by Meichenbaum (1977). The SIT method provides an overview for treating and preventing of stress and anxiety among postgraduate students. It provides support and describes the potential role of therapeutic recreation in the development of stress management and anxiety control. The objective of this study is to examine the effectiveness of SIT program on stress, anxiety and coping strategies level of postgraduate students.This research was carried out in the Faculty of educational studies of Universiti Putra Malaysia. The population of the study was all postgraduate students enrolled in this Faculty in the academic year of 2012-2013. The present study used experimental design to achieve its objectives. Simple random sampling was employed to achieve high level stress and anxiety among postgraduate students in thefaculty of education. Sixty four students with high level stress and anxiety were randomly assigned to each group, 32 of the respondents were participated in experimental group and 32 of them were participated in control group. The instruments of the study werePerceived Stress Scale (PSS14) for measuring the levels of stress, State-Trait Anxiety Inventory (STAI-Y) for measuring the levels of anxiety, and Ways of Coping Scale (WOCS) for coping strategies. SPSS version (20) was the analytical tools used in this study. The results of repeated measure ANOVAshowed that the interaction between group and test was statistically significant for stress, anxiety and eight dimensions of coping strategies. Furthermore, the results of mean comparison between experimental and control groups in pre and posttest using t-test (independent and paired)showed that the level of respondent’s stress and anxiety were reduced significantly by SIT program. The results also revealed that SIT program increasedsignificantly six dimensions of coping strategies including confrontive coping, seeking social support, accepting responsibility, self-controlling, planful problem-solving, and positive reappraisal, while, decreased two dimensions of coping strategies including distancing and escape-avoidance.The findings from this research can provide information to those who intend to plan beneficial programs for the university students to improve their academic performance regarding to treatment of anxiety, management of stress, and development their coping strategies.